Green and efficient sulfur dioxide removal using hydrogen peroxide in rotating packed bed reactor: Modeling and experimental study. (18th May 2021) - Dong, Yu-Ning; Chen, Wen-Cong; Zhang, Liang-Liang; Sun, Bao-Chang; Zou, Hai-Kui; Luo, Yong; Chu, Guang-Wen; Chen, Jian-Feng
Graphical abstract: Highlights: A mathematic model was first developed to describe mass transfer process in RPB. The outlet SO2 concentration was ultra-low, below 35 mg/m 3 . The predicted desulfurization efficiency agreed well with the experimental result. The HTU for RPB is one order of magnitude lower than that of conventional reactors. Abstract: In order to reduce SO2 emissions and achieve green utilization of sulfur resources, a desulfurization method of SO2 removal using hydrogen peroxide (H2 O2 ) in rotating packed bed (RPB) is proposed. It can not only achieve the efficient removal of SO2, but also lead to the effective utilization of sulfur resources. A mathematic model was first developed to describe the reaction and mass transfer process between H2 O2 and SO2 in RPB. The influences of different operating conditions including RPB rotating speed, H2 O2 mass fraction, gas–liquid volumetric flow rate ratio, gas flux, and inlet SO2 concentration on desulfurization performance were studied. Under the optimized conditions, it turned out that the desulfurization efficiency was above 99% and the outlet SO2 concentration was ultra-low, below 35 mg/m 3 . The validity of the model was confirmed by the fact that most of the predicted desulfurization efficiency agreed well with the experimental result with a deviation within 5%. The height of mass transfer unit HTU for RPB is calculated to be 1.60–2.07 cm, which is one order of magnitude lower than that of conventional reactors, indicating the investment of the desulfurization reactor can be greatly reduced by using RPB.